Organization career guidance in the «school – high school» (Pedagogy of Higher and Secondary Education, 2014)
Bondarenko О. V. Organization career guidance in the «school – high school».The article highlights the key aspects of the organization of vocational guidance in the «school – university». Author disclosed the contents, methods and forms of career guidance, carried out an analysis of factors affecting the profile, and subsequently senior professional choice.
Keywords: vocational guidance; professional-oriented work; vocational self-determination; choice of profession; career guidance system; forms and methods of vocational guidance